2013
DOI: 10.2109/jcersj2.121.934
|View full text |Cite
|
Sign up to set email alerts
|

Effect of particle size of tabular talc powders on crystal orientation and sintering of cordierite ceramics

Abstract: Cordierite ceramics were prepared from several types of kaolin powders and talc powders having various median particle size with nanometer-sized alumina sol. Powder mixtures were uniaxially pressed, followed by cold isostatic pressing to make thin compacts. Crystal orientation of talc particle and resultant cordierite were evaluated using the X-ray diffraction profile measured on the uniaxially pressed surface of calcined compacts and sintered compacts, respectively. Coarser talc powders above 3¯m aligned thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…However, the finest PSD is represented in BT3, BT4 and BT5 samples (90wt.% of the PSD is below 20.20, 23.20 and 26.80μm, respectively). For solid-state sintering, the fine particle grain size enhances the densification and the development of higher liquid phases at low sintering temperatures [50][51][52]. Therefore, BT3, BT4 and BT5 samples would be densified and had higher liquid phase at lower temperatures compared to other samples.…”
Section: Raw Materials and Batch Characterizationmentioning
confidence: 99%
“…However, the finest PSD is represented in BT3, BT4 and BT5 samples (90wt.% of the PSD is below 20.20, 23.20 and 26.80μm, respectively). For solid-state sintering, the fine particle grain size enhances the densification and the development of higher liquid phases at low sintering temperatures [50][51][52]. Therefore, BT3, BT4 and BT5 samples would be densified and had higher liquid phase at lower temperatures compared to other samples.…”
Section: Raw Materials and Batch Characterizationmentioning
confidence: 99%
“…However, the nest PSD is represented in BT3, BT4 and BT5 samples (90wt.% of the PSD is below 20.20, 23.20 and 26.80μm, respectively). For solid-state sintering, the ne particle grain size enhances the densi cation and the development of higher liquid phases at low sintering temperatures [50][51][52]. Therefore, BT3, BT4 and BT5 samples would be densi ed and had higher liquid phase at lower temperatures compared to other samples.…”
Section: Raw Materials and Batch Characterizationmentioning
confidence: 99%
“…On the other hand, the coefficient of volume expansion of the composites decreased when increasing the nano talc content as depicted in Figure 5(d). It was due to superior thermal resistance of the nano talc that prevented the expansion of the composites during the elevated temperature [42,43]. It has been reported that the addition of mineral fillers in 3D printing filaments decreased the coefficient of volume expansion, which contribute for improving printability, reducing warpage, shrinkage, and printing defects in the 3D printing process [3].…”
Section: Specific Volume and Coefficient Of Volume Expansionmentioning
confidence: 99%